TELAAH KRITIS KINERJA KEPALA DESA DALAM PELAYANAN PUBLIK DESA PENYARING KECAMATAN MOYO UTARA - Marisa Sutanty; Sri Rahayu; Mega Lestia; I Nyoman Sutama (Samalewa: Jurnal Riset & Kajian Manajemen, 2021)
This study aims to know the quality of public services provided by the Head Village of Penyaring Village, Moyo Utara Sub-District. Type of this study was descriptive. The type of data used in this study was qualitative data obtained through interviews. The informants in the study were the community and government staff in Penyaring Village, Moyo Utara Sub-District. Data analysis was done using data analysis techniques of Miles and Huberman which consisted of data collection, data reduction, data presentation and drawing conclusions. The validity of the data was tested using triangulation. The results of study showed that the performance of the head village in the public service of Penyaring village, Moyo Utara Sub-district was still not good, due to the lack of village officials in several positions so that it was not optimal in service, the lack of discipline of the Head village in working hours caused public service not optimal. The  hope of Penyaring Village community, especially in providing services, must comply with village regulations, and the mechanism for making decisions and policies must prioritize the community, not groups.